Perancangan dan Implementasi Repositori Gambar Digital Berbasis Web Menggunakan React.js dan Laravel - Poozasya Niagaralillah; Muhamad Fikri (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
The development of web technology has increased the need for digital data storage and management systems that can be accessed online. One form of such systems is a web-based digital image repository that allows users to store, search, view, and download image collections efficiently. This study aims to design and implement a web-based digital image repository using React JS as the frontend and Laravel as the backend supported by RESTful API. The system development method used is the Waterfall method, which includes requirement analysis, system design, implementation, and testing stages. The results show that the system successfully provides core features such as gallery display, image search, and image download. Functional testing indicates that the search and download features work properly according to user needs. Although the login and upload features are still under development, the system has generally achieved the research objective as an accessible and efficient web-based digital image repository